ANALYSIS OF THE EFFECTIVENESS OF THE LAPOR APPLICATION IN COMMUNITY SATISFACTION COMPLAINTS AT THE SIDOARJO REGENCY REGIONAL SECRETARIAT OFFICE - Zahira, Ghania Nasha; Choiriyah, Ilmi Usrotin (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research investigates how well the LAPOR application (People’s Online Aspiration and Complaint Service) functions as a tool for managing public complaints at the Sidoarjo Regency Regional Secretariat. As a component of the National Public Service Complaint Management System (SP4N-LAPOR), the application aims to improve transparency, accountability, and public engagement in service delivery. Method: Employing a qualitative descriptive method through interviews, observations, and document reviews, the research included key participants such as application coordinators, service personnel, and user groups. The data were analyzed using Campbell’s effectiveness criteria, which encompass program effectiveness, achievement of goals, balance between inputs and outputs, and overall performance. Results: The results indicate that LAPOR speeds up the process of addressing complaints and protects the privacy of those making complaints; however, issues persist, such as unreliable internet access, reliance on central servers, and minimal public engagement stemming from insufficient outreach and limited digital skills. While there are enough human resources, the system still falls short of its full potential effectiveness, indicating a need for strategies to enhance literacy, outreach efforts, and technological infrastructure. Novelty: The study highlights both the practical benefits of LAPOR in speeding up complaint handling and protecting user privacy, as well as the persistent challenges that hinder full system effectiveness, offering insights for targeted improvements in digital literacy, outreach, and infrastructure.